Effect of ethyl acetate extract of usnea longissima on esophagogastric adenocarcinoma in rats - Mammadov,Renad (2019)
Abstract Purpose: To investigate the effects of the EtOAc extract of U. longissima which is uninvestigated previously on esophagogastric cancer induced in rats with N-methyl-N-nitro-N-nitrosoguanidin (MNNG). Methods: The anticancer activity of EtOAc extract of U. longissima was examined in the esophagogastric adenocarcinoma models induced in rats with MNNG. EtOAc extract of U. longissima, 50 and 100 mg/kg oral doses were administered once daily for six months. MNNG induced differentiated and undifferentiated type adenocarcinomas in the esophageal and gastric tissues of rats. Results: EtOAc extract of U. longissima obtained from U. longissima prevented gastric and esophageal cancerogenesis induced in rats with MNNG. EtOAc extract of U. longissima did not have a lethal effect at doses of 500, 1000 and 2000 mg/kg. The prominent anticarcinogenic activity of EtOAc extract of U. longissima 50 and 100 mg/kg suggests that it is not toxic and it is selective to the cancer tissue. Conclusion: This information may shed light on clinical implementation of EtOAc extract of U. longissima in future.